FAKTOR KONSUMSI DALAM EKONOMI ISLAM - Hisan, Dewi Ghitsatul; Haniatunnisa, Siti (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2023)
The foundation of Muslim consumer behavior is different from conventional consumers. This paper aims to find out how the consumption factor is in an Islamic perspective and its differences in a conventional perspective. This paper uses a qualitative descriptive approach with a literature study for data collection. Conventional consumers emphasize maximum satisfaction and efforts to fulfill needs and desires without restrictions. In contrast to Muslim consumers who have limitations in their consumption activities and strive to achieve optimal maslahah levels. Humans as rational man in conventional economics, and as Islamic man in Islamic economics. This also results in a difference between needs and wants.